COMPARING TRANSLATION PRODUCTS OF DIFFERENT LANGUAGES BIBLE: A NEW METHOD IN BIBLICAL HERMENEUTIC - Yandres Lao (Postgraduate School, Universitas Nusa Cendana, 2019)
This article proposes new method in Bible interpretation by comparing translation products of Bible which are reflected in many different languages. This writing is also a result of a research which found that comprehending Bible does not demand only its original languages (Hebrew and Greek), however, national languages and local ones may also be used to explore the meaning carried in the Bible by comparing them. The content of this piece of writing provides two main techniques in the new method of Bible comprehension. They are grammatical comparison of languages and historical context as a confirmation. At first, texts of Bible in different languages (the writer uses English, Indonesian, and Kupang Malay text) are compared on each level of the language (word, clause, sentence, and figurative language) to portray the grand idea of the texts; and the next is confirming it to the historical context of the text. This new method contributes to the development of hermeneutics more specifically in Biblical exegesis. Furthermore, this new concept will raise local languages into the higher level, meaning that local languages will be widely used in Bible comprehension with national language of readers and original languages of Bible. This help keep the existence of local wisdom including languages.